The Benefits of Revealing Race: Evidence from Minority-Owned Local Businesses - Aneja, Abhay; Luca, Michael; Reshef, Oren (American Economic Review, 2025)
Is there latent demand to support Black-owned businesses? We explore this question by analyzing a new feature that made it easier to identify Black-owned restaurants on an online platform. We find that labeling restaurants as minority-owned increased customer engagement and firm performance, as measured by online traffic, calls, orders, and in-person visits. These effects were more pronounced in areas characterized by greater support for the Democratic Party and lower implicit bias against racial minorities. Labeled restaurants also see an increase in the fraction of reviews that are written by White customers. (JEL D22, J15, L25, L83, L86)